The safety and efficacy of intravenous administration of tranexamic acid in off-pump coronary artery bypass grafting: a systematic review and meta-analysis - Zou, Zhi-yao; Song, Jin-rui; Zhang, Qing-Hui; Huang, Xiao-Jin; Yao, Yun-tai (Frontiers in Medicine, 2025)
Study objectiveTo assess the efficacy and safety of tranexamic acid (TXA) on off-pump coronary artery bypass (OPCAB) surgery.DesignMeta-analysis.MethodsRelevant trials were identified by computerized searches of PUBMED, Cochrane Library, EMBASE, OVID, China National Knowledge Infrastructure (CNKI), Wanfang Data and VIP Data till Aug 8th, 2025, were searched using search terms “Tranexamic acid,” “coronary artery bypass grafting,” “off-pump,” “randomized controlled trial” database search was updated on Aug 10th, 2025. Primary outcomes included intraoperative and postoperative bleeding.ResultsNineteen randomized controlled trials were finally included in the current study. Intravenous TXA reduced intraoperative and postoperative bleeding volume (including 2, 4, 6, and 24-h postoperative bleeding). It also decreased the rate and volume of red blood cell (RBC) and fresh frozen plasma (FFP) transfusions, with no effect on reoperation rates due to postoperative bleeding. At 24 h postoperatively, TXA increased platelet counts, hemoglobin concentrations, and prothrombin time (PT), while decreasing activated partial thromboplastin time (APTT), fibrinogen levels, and D-dimer concentrations. Importantly, TXA did not elevate the risk of postoperative complications (e.g., mortality, myocardial infarction, cerebrovascular accidents, thrombotic events) and had no impact on levels of CK-MB, creatinine, interleukin-6, or lengths of intensive care unit (ICU) and hospital stays.ConclusionIntravenous TXA is effective in reducing perioperative bleeding and transfusion requirements in OPCAB without increasing the risk of major postoperative complications, supporting its clinical utility in this setting. More well-designed and adequately powered RCTs are needed to confirm this further.